(untitled) (World Bulletin of Management and Law, 2023)
This article delves into the international legal regulation of international commercial arbitration and the various multilateral and bilateral agreements that govern this field. The paper examines the enforcement and recognition of arbitral awards, the selection of arbitrators, and the role of international organizations in promoting international commercial arbitration. It also discusses the challenges faced in implementing these agreements and the potential for future developments in this area, in addition provides a succinct analysis of the crucial role of international legal regulation in facilitating international trade and commerce through commercial arbitration.